Social isolation experienced by postpartum women during the Covid-19 pandemic (Research, Society and Development, 2021)
Objective: To know the positive and negative aspects of social isolation experienced by postpartum women during the Covid-19 pandemic. Methodology: A qualitative research was carried using the Grounded Theory as methodological framework. 14 postpartum women who gave birth in a hospital in southern Brazil participated. Data were collected in the second half of 2020 through interviews, being analyzed using open, axial and selective coding. Results: As positive, they reported being able to conduct their actions with their baby no intrusion; less concern about contagion by Covid-19. They reported tranquility to establish breastfeeding. They were able to meet the needs of their children of different ages, their intimacy preserved. They recognized as negative the need for social isolation and adhered to protective measures for fear of contagion. They manifested needs for emotional interaction and desire to share the joy of their child's birth with other people. They experienced the puerperium was a solitary, insecure and exhausting, felt the lack of a support network, feeling overloaded with the demands of the baby, household chores, having to manage their feelings. Final considerations: Social isolation had a strong impact on the puerperium experience, requiring changes in plans and adaptations. The use of alternative forms of contact should be implemented online media a way to keep them in social contact even if they are far away. The partner must be equipped to care for both the mother and the newborn, minimizing their physical and mental strain.